Житие Иоанна Готского из Минология Василия II - Могаричев, Ю.М.; Шапошников, А.К. (Хазарский альманах, 2014)
Житие Иоанна Готского – один из ключевых источников для изучения истории Крымского полуострова «хазарского периода». Его первоначальной версии не сохранилось. Наиболее полная из дошедших до нас редакций – вероятно, сокращенный вариант Жития, состоящий из десяти небольших отрывков (глав). Vita of John of Gothia is one of the key source for studying history of Crimean peninsula in “Khazar Period”. Synaxarium abridge of his Life that is situated in Menologion of Basil II remained mainly unheeded by scholars. In this article being analyzed this source. The authors concluded that this text is one of the earliest narratives about John of Gothia. It also is abridge from Synaxarium Ecclesiae Constantinopolitanae. Because of that fact, it can`t be independent source of trustworthy information.